The economics of forest restoration: A cost-effectiveness analysis of the leasehold forestry programme in Nepal - Sony Baral; Santosh Paudel; Bijendra Basnyat; Rajesh K Rai (Trees, Forests and People)
In recent decades, Nepal's forest cover has increased significantly, primarily attributable to the community-based forest management approach. The Leasehold Forestry Programme (LFP) has been in place for three decades to reduce poverty. Given that the dynamics of forest ecosystems and socio-economic conditions evolve over time, it becomes imperative to evaluate not just whether the program achieves its original goals, but also whether it contributes to deliver ecological benefits and restoration outcomes in a cost-effective manner. However, the existing literature on cost effectiveness predominantly centres around community forestry. Therefore, this research comprehensively examined the cost-effectiveness of the LFP using a cost benefit analysis, focusing on case studies from Nepal's Gorkha, Tanahun and Nawalpur districts in the Chitwan Annapurna Landscape. For this study, 64 user groups were selected from 921 leasehold forests, using a three-stage cluster sampling technique. A household-level semi-structured questionnaire interview (n = 154 for control forest users and n = 320 for leasehold forest users) was conducted to ascertain the costs and benefits for the beneficiary households. Except for the carbon benefit, which was determined through a field-based biomass survey, we employed the benefit transfer approach for regulatory forest ecosystem services. The results indicate that leasehold forests perform better economically and contribute to the enhancement of user livelihoods compared to control forests. Emphasizing the leasehold programme's goal of ensuring fair access to and distribution of resources, this study underscores the importance of tenure certainty as a crucial factor in attracting prospective tenants and offering security for funding land restoration projects. However, recent modifications of the leasehold forestry tenure limit may impact the programme's future effectiveness.